2018
DOI: 10.1186/s12967-018-1433-7
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical feasibility of umbilical cord tissue-derived mesenchymal stem cells in the treatment of multiple sclerosis

Abstract: BackgroundMultiple sclerosis (MS) is a progressively debilitating neurological condition in which the immune system abnormally erodes the myelin sheath insulating the nerves. Mesenchymal stem cells (MSC) have been used in the last decade to safely treat certain immune and inflammatory conditions.MethodsA safety and feasibility study was completed on the use of umbilical cord MSC (UCMSC) as a treatment for MS. In this 1-year study, consenting subjects received seven intravenous infusions of 20 × 106 UCMSC over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 36 publications
0
110
0
4
Order By: Relevance
“…Another property of MSCs is their anti-infl ammatory and immunosuppressive effects. A large number of preclinical studies (Alunno et al, 2015;Yang et al, 2016;Zhang et al, 2017) and clinical studies (Dahbour and Jamali, 2017;Riordan et al, 2018;Zhang et al, 2018) have shown that MSCs considerably alleviate symptoms of autoimmune diseases. Compared with stem cells from other sources, umbilical cord mesenchymal stem cells possess advantages, including rapid, non-invasive harvest procedures, easy expansion in vitro, and ethical access; additionally, umbilical cord mesenchymal stem cells exhibit robust immunosuppressive functions (Jin et al, 2013;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another property of MSCs is their anti-infl ammatory and immunosuppressive effects. A large number of preclinical studies (Alunno et al, 2015;Yang et al, 2016;Zhang et al, 2017) and clinical studies (Dahbour and Jamali, 2017;Riordan et al, 2018;Zhang et al, 2018) have shown that MSCs considerably alleviate symptoms of autoimmune diseases. Compared with stem cells from other sources, umbilical cord mesenchymal stem cells possess advantages, including rapid, non-invasive harvest procedures, easy expansion in vitro, and ethical access; additionally, umbilical cord mesenchymal stem cells exhibit robust immunosuppressive functions (Jin et al, 2013;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The preclinical data on MSCs both alone and in conjunction with other treatment strategies are promising. These cells have entered at least Phase I (safety) clinical trials for multiple nervous system diseases and injuries, most notably cerebral ischemia, multiple sclerosis, Alzheimer's disease, and TBI . While we have a better understanding of the pathologic cascades triggered after TBI and the mechanisms by which MSCs repair the brain and improve functional outcomes, we are still years away from realizing an effective regenerative medicine therapy for TBI that is widely available to patients.…”
Section: Resultsmentioning
confidence: 99%
“…The experience of allogenic MSC therapy in MS is very limited. A few reports have shown promising results of allogenic umbilical cord (UC) MSC therapy in MS [57]. Allogenic UC MSC may enable a more accessible and practical supply of cells for infusion compared to allogenic BM MSC.…”
Section: Discussionmentioning
confidence: 99%